Pengembangan Handout PAI Berbasis Nilai Dinamis dan Inovatif untuk Pemahaman Islam Wasathiyah di SMKN 1 Jombang - Yunizhar, Laili; Zulfah, Machnunah Ani (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
The application of Wasathiyah Islamic principles in the learning process can be a solid foundation for forming inclusive understanding, overcoming radicalism, and encouraging dynamic and innovative values among Muslims. Therefore, this research has an important role in understanding the concept of Wasathiyah Islam as a strategy to prevent radicalism, by adopting a dynamic and innovative values approach through Handout distribution. The aim of this research includes two main aspects. First, developing a product in the form of a handout as material for teaching Islamic Religious Education based on dynamic and innovative values for class X students at SMKN 1 Jombang. Second, evaluating the effectiveness of PAI teaching materials in the form of handouts that focus on dynamic and innovative values in understanding Wasathiyah Islam on the learning interests of class X students at Vocational Middle School (SMKN) 1 Jombang. The research carried out implemented R&D (Research and Development) development, namely 4D. The assessment instruments included material validation instruments, student response questionnaires to handout teaching material media, as well as pretest and post-test questions. The results of the analysis show that the dynamic and innovative values of Wasathiyah Islam can be effectively integrated into the handout, forming a deeper and more comprehensive understanding of the concept.